THE INFLUENCE OF WORK DISIPLINE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE IN PT. YAMAHA MUSIC MANUFACTURING ASIA - Agung Surya Dwianto; Widayatmoko Widayatmoko; Nur Aini (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Work discipline and organizational culture are important issues that have always been the main focus of every company, because they are closely related to overall performance. Many things are done by the organization in order to improve the work discipline of its employees and improve organizational culture, one of which is to commit to implementing mutually agreed provisions. Because with a high commitment to implement all existing provisions, this will have an impact on the decreasing number of errors that arise, so that it will have a significant effect on the company's performance. PT. Yamaha Music Manufacturing Asia is a manufacturing company that produces musical instruments, where most of its production is intended for overseas markets. Not much different from what is experienced by other manufacturing companies, PT. Yamaha Music Manufacturing Asia also has problems with discipline issues and the implementation of a quality organizational culture. The purpose of this study was to determine the effect of work discipline and organizational culture on the performance of employees of PT. Yamaha Music Manufacturing Asia. This study uses a quantitative approach with data collection methods by distributing questionnaires to 165 employees of the production department of PT. Yamaha Music Manufacturing Asia. The results showed that there was a significant influence, work discipline variables and organizational culture on the performance of employees of PT. Yamaha Music Manufacturing Asia by 70.7%.